Mini review: Advances and challenges in CAR-T cell therapy: from early chimeric antigen receptors to future frontiers in oncology - Ceballos, Candela; Viguria, Mª Cruz; Panizo, Carlos; Rodríguez-Madoz, Juan Roberto; Prósper, Felipe (Frontiers in Hematology, 2023)
Cell therapy utilizing chimeric antigen receptors (CARs) in conjunction with immune cells, primarily T lymphocytes, is known as CAR-T cell therapy. This innovative approach is revolutionizing the landscape of oncohaematology by precisely targeting specific antigens for elimination. However, despite its promising prospects, CAR-T therapy presents several challenges, including a notable rate of disease relapse, intricate pathologies impeding widespread adoption, prolonged manufacturing timelines, and substantial costs. Looking forward, ongoing research and progress aim to address these challenges to mitigate these constraints, underlining the continuous efforts to enhance the efficacy and accessibility of this transformative therapy.